2017
DOI: 10.3389/fneur.2017.00073
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Correlates of Task-Specific Dystonia in a Large Cohort of Brazilian Music Players

Abstract: Musician’s dystonia is a task-specific dystonia (TSD) worldwide disabling disorder, and most of the affected individuals may have severe difficulty to play their instrument. Many professional music players may have to quit working as a player. The objective of the present study was to evaluate the clinical characteristics and frequency of TSD in Brazilian music players and to promote awareness of this condition among musicians. We visited orchestras and music schools delivering lectures on TSD and about the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Professional musicians often suffer from physical and psychological problems related to the combination of strenuous training and psychological vulnerability (Spahn, Voltmer, Mornell, & Nusseck, 2017). These problems include musculoskeletal pain (Jacukowicz, 2016), hearing loss (Hasson, Theorell, Liljeholm-Johansson, & Canlon, 2009), dystonia (Iltis et al, 2016; Moura, de Carvalho Aguiar, Bortz, & Ferraz, 2017), depressive states (Vaag, Bjørngaard, & Bjerkeset, 2016), and mental disorders (Mula & Trimble, 2009). Alcohol and illegal drugs (e.g.…”
mentioning
confidence: 99%
“…Professional musicians often suffer from physical and psychological problems related to the combination of strenuous training and psychological vulnerability (Spahn, Voltmer, Mornell, & Nusseck, 2017). These problems include musculoskeletal pain (Jacukowicz, 2016), hearing loss (Hasson, Theorell, Liljeholm-Johansson, & Canlon, 2009), dystonia (Iltis et al, 2016; Moura, de Carvalho Aguiar, Bortz, & Ferraz, 2017), depressive states (Vaag, Bjørngaard, & Bjerkeset, 2016), and mental disorders (Mula & Trimble, 2009). Alcohol and illegal drugs (e.g.…”
mentioning
confidence: 99%
“…Among 22 wind players, 16 reported ED (70%). 11 In another study of 119 musicians with musician dystonia (MD), ED was observed in 19% of the patients. 12 In a study of 585 brass musicians, 68% of musicians reported embouchure problems.…”
Section: Epidemiologymentioning
confidence: 99%
“…Task-specific dystonia (TSD) is a focal dystonia of a body part that is associated with a specific activity. For example, focal dystonia of the arms and hands or oromandibular muscles was observed most frequently in players of acoustic guitar or brass instruments during their performance, which is often called musician’s dystonia [109]. Isolated lingual dystonia induced by speaking [110] or OMD induced by praying [111] are also found in TSD.…”
Section: Dystoniamentioning
confidence: 99%
“…Since dystonia usually does not occur during other tasks, dysphagia in TSD is less frequent even in patients whose oromandibular muscles are affected. However, the symptoms can progress and involve swallowing functions over time [109].…”
Section: Dystoniamentioning
confidence: 99%